2014
DOI: 10.5267/j.msl.2013.11.037
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of emotional intelligence on retail investors’ behavior

Abstract: Investment decisions are normally accomplished based on fundamental or technical methods. However, there are many cases where investors make their investment decisions based on their emotions. This study investigates the effects of various factors including biases representation, mental accounting and risk aversion when an investment decision is executed. In other words, the study examines the effects of emotional intelligence components on retail investors' investment strategies on Tehran Stock Exchange (TSE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Pervez (2014) found that the lively understanding attributes of the cash related specialists are related to experience choices of the scholars. Pirayesh (2014) assessed the effect of stimulating information on theoretical frameworks of retail money related specialists in the Tehran Stock Exchange. He construed that there was a positive connection between stimulated learning and hypothesis decisions.…”
Section: Behavioral Biasesmentioning
confidence: 99%
“…Pervez (2014) found that the lively understanding attributes of the cash related specialists are related to experience choices of the scholars. Pirayesh (2014) assessed the effect of stimulating information on theoretical frameworks of retail money related specialists in the Tehran Stock Exchange. He construed that there was a positive connection between stimulated learning and hypothesis decisions.…”
Section: Behavioral Biasesmentioning
confidence: 99%
“…Okpara and Edwin (2014) found that workplace EI influence the return on investment. Pirayesh (2014) examined the effect of EI on investment strategies of retail investors in Tehran Stock Exchange. The data was collected from 270 investors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ezadinea, Fathi, and Salami [28] also demonstrated the effects of EI on financial behavior biases and investment performance. Pirayesh [29] carried out an empirical study from which it was concluded that there was a relationship between global EI and the investors' decision, pointing out that investors with a high level of EI had a greater riskaversion, understood as mistrust that the individual manifests to accept an offer with an uncertain result compared to another offer with a less profitable but safer result [30]. On the other hand, Tanvir, Sufyan, and Ahsan [31] used Goleman's (1998) five dimensions of EI and demonstrated that there was an influence of global EI and some emotional competencies (emotion regulation, self-motivation, and trait empathy) in the investor decision-making process.…”
Section: Emotions and Financial Behaviormentioning
confidence: 99%
“…Finally, and referring to global EI, we were also able to observe a deficit of students with respect to professionals. This aspect can lead them to have greater endowment bias, self-control, optimism bias, risk aversion, and regret aversion [29]. On the contrary, and due to this deficit in global EI, students were more risk averse than professionals, so they may tend not to analyze investment risk well.…”
Section: Impact Analysismentioning
confidence: 99%